Developing An Interactive PowerPoint as Supporting Media for Teaching Procedure Text - Nursabila, Aulia Nizar; Bahtiar, Yuyun; Fikri, Akhmad Kanzul; Hanifah, Hanifah (APPLICATION: Applied science in Learning Research, 2024)
This study aimed at developing the learning media named an interactive PowerPoint. It is a supporting media for teaching of Procedure text for Grade VII of Junior High School Private 7 Nganjuk. The media could help students get better understanding about Procedure text and the students did not get bored during the class. The media also led students feel joyful in the learning process. The research method applied at this study was Research and Development (R&D) that adapted ADDIE model that consisted of five procedures. They are 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. This study involved 32 students of Grade VII A at Junior High School Private 7 Nganjuk. The results of the study are categorized good in term of media validation (score 66), material validation (score 63), and respondent (score 65). It can be summed up that the use of interactive PowerPoint as supporting media for teaching of Procedure text is worth to apply.